Detection, Antimicrobial Susceptibility and Serotyping of Streptococcus pneumoniae from Cerebrospinal Fluid Specimens from Suspected Meningitis Patients - Alam, M Rabiul; Saha, Samir Kumar; Nasreen, Tania; Latif, Farzana; Rahman, Sabita Rezwana; Gomes, Donald James (Bangladesh Journal of Microbiology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Pneumococcal meningitis is the most important cause of community-acquired meningitis in children resulting in high morbidity and mortality worldwide. This study aimed to evaluate immunochromatographic test (ICT), a rapid detection method, for pneumococci in cerebrospinal fluid (CSF) and also to assess antibiotic susceptibility pattern of the clinical isolates. The findings of CSF-ICT of suspected meningitis cases were also compared with the results of CSF culture, latex agglutination test (LAT) and polymerase chain reaction (PCR). Among these diagnostic methods, ICT and PCR showed 100% specificity. A total of 401 CSF specimens were cultured but culture positivity was observed with 55 (13.7%) cases in which Streptococcus pneumoniae was identified from 20 (36.4%) culture-positive cases. A remarkably high resistance rate to gentamicin (95%) and cotrimoxazole (60%) among the invasive strains of S. pneumoniae was observed, while none of the isolates exhibited resistance to penicillin, ceftriaxone and chloramphenicol by disk diffusion test. Minimum inhibitory concentration (MIC) showed similar susceptibility pattern. The invasive strains (n = 18) belonged to 9 different serotypes including 1, 2, 4, 34, 12A, 38, 19F, 35A and 45. The prevalent serotypes were 2 (23.5%), 1 (17.6%) and 45 (11.8%). The study shows that a remarkable proportion of meningitis cases in children are caused by S. pneumoniae. Diagnostic methods like ICT and PCR can be considered as effective methods for the detection of pneumococcal meningitis even with the patients who have been treated with empirical antibiotics. Ceftriaxone is a safe choice for empirical therapy, while the use of cotrimoxazole for the treatment of meningitis infections is debatable. Keywords: Pyogenic meningitis, Cerebrospinal fluid (CSF), Streptococcus pneumoniae Immunochromatographic test (ICT), Polymerase chain reaction (PCR), Serotying DOI: http://dx.doi.org/10.3329/bjm.v24i1.1232 Bangladesh J Microbiol, Volume 24, Number 1, June 2007, pp 24-29